(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to clarify the sources of non-deposit financing (cash insurance, revenue allocation, other revenues, long-term loans, and miscellaneous allocation) in controlling the use of capital because it is (the ratio of capital to total deposits, the ratio of capital to assets, and the risk capital disclosure, The ratio of capital to total assets, the ratio of total non-deposit financing sources to total requests, the ratio of capital to total non-deposit financing sources) and a statement of their impact on the so-called. The problem of the research lies in the lack of vision among commercial banks about the importance of non-deposit sources of financing, in addition to the other basic sources of banks, which are capital, reserves, and cash deposits of all kinds, and the extent of their direct impact on the financing structure and the adequacy of banking capital. Accordingly, the above indicators were analyzed based on financial statements of the researched bank listed on the Iraqi Stock Exchange for the period from (2016 - 2021), The research reached several conclusions, the most important of which is the existence of a very weak relationship between non-deposit financing sources and the adequacy of bank capital. The study recommended a number of recommendations, the most important of which was making optimal use of non-deposit financing sources to achieve the greatest possible degree of profitability enhancing capital adequacy. The Bank of Baghdad was chosen as one of the oldest commercial banks in Iraq, with its good reputation and the integration of its financial data within the Iraqi Stock Exchange It practices all types of banking operations and keeps pace with developments in the banking field, as this period was chosen to demonstrate the extent of the impact of cash insurance and the income tax provision on the adequacy of banking capital.